The RELATIONSHIP OF HALAL AWARENESS, SELECTION OF MENU VARIATION AND NUTRITION KNOWLEDGE WITH PURCHASE DECISIONS: A STUDY ON CHATIME CONSUMERS IN SURABAYA - Palupi, Olvi Aprilia; Putri, Endah Budi Permana (UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2022)
Boba drinks attracts people's attention to consume it. Surabaya is one of the big cities visited by a boba franchise company, namely the Chatime brand. The purpose of this study to analyzed the relationship between halal awareness, selection of menu variations and nutrition knowledge with purchasing decisions on Chatime brand boba drinks. This research method used analytic observational with a cross-sectional type of research. The sample in this study amounted to 162 respondents who were partly students in the city of Surabaya with the accidental sampling method. Collecting data using a questionnaire. The data analysis performed was univariate and bivariate analysis using the Spearman rank test. The results showed that halal awareness was good (61,7%), selection of menu variation was good (35.8%), nutrition knowledge was good (61.1%) and purchasing decisions was enough (47.5%). The results show there was a significant relationship between halal awareness and the purchasing decision of Chatime boba drinks (p-value = 0.002), there was a significant relationship between the selection of menu variations and the purchasing decision of Chatime boba drinks (p-value = 0.000), there was no relationship between nutrition knowledge and purchasing decisions of Chatime boba drink (p-value = 0.489). The conclusion in this study is that there was a relationship between halal awareness and purchasing decisions. There was a relationship between the selection of menu variations with purchasing decisions. There was no relationship between nutrition knowledge and purchasing decisions. Keywords: boba drink, halal awareness, purchasing decisions.